Investigating eye-strain due to prolonged exposure to low resolution multimedia using LSFG - Bhatti, M.S. (Institute of Electrical and Electronics Engineers Inc., 2017)
Gazing at computer screen for long hours may cause eye strain. The strain goes away after the eyes have been relaxed and kept away from the screen for some time; however, prolonged exposure may cause dryness and irritability. The eye-strain is monitored by a laser speckle flowgraphy (LSFG) system in this study. The LSFG system measures and displays choroidal vascular maps providing relative blood flow readings. The results show consistently high erythrocyte movement after watching low definition and low quality video for long time. Moreover, it is also observed that the blood flow tends to stabilize itself after relaxing the eyes for a couple of hours. © 2016 IEEE.